High tension electrocution death: New histopathological cardiac tools by Confocal Laser Scanning Microscope. (August 2019) - De Donno, Antonio; Favia, Matteo; Marzullo, Andrea; Mele, Federica; Introna, Francesco
Abstract: In deaths due to electrocution intraepidermal separation, vacuolation of epidermal cells, "swiss cheese" aspect of the superficial part of epidermis (swollen and with multiple vescicles), metallization, necrosis of collagenous fibers, cardiomyocytes alterations are microscopically described. No cardiac nerve damage due to electricity is actually reported in literature. In this work we tried to find new morphological signs in the hearts of deaths due to electrocution. In three cases of deaths due to electrocution, in which forensic autopsies were performed within 36 h of the death, heart specimens were taken at the level of common trunk of the left coronary artery. The myocardium histological examination at optical microscope and Confocal Laser Scanning Microscope (CLSM) revealed fragmentation of cardiomyocytes, nerve trunks damage with hydropic swelling of the nerve fibers, interstitial and sub-nerve-sheath edema, very dishomogenous distribution of the natural fluorescence of the neurofilaments, coarctation of epicardial gangliar cells with cytoplasmic cleft and irregular fluorescence pattern. Identification of S-100 protein by immunohistochemistry can help to better observe the hydropic swelling of the nerve fibers and the central cytoplasmic clefts. These alterations could be used in future as specific signs of the passage of the electrical current through the heart. We recommend heart specimens at the level of common trunk of the left coronary artery in all the cases of suspected electrocution, to better evaluate cardiac nerve trunks damages and alterations. Highlights: Deaths due to electrocution do not have specific findings at the autopsy. No cardiac nerve damage due to electricity is actually reported in literature. The optical microscope and Confocal Laser Scanning Microscope (CLSM) examination allow us to find new interesting features.